58 Effects of sodium–glucose co-transporter 2 (SGLT2) inhibitors on major cardiovascular events in Type 2 diabetic patients: a meta-analysis of randomized controlled trials. (8th December 2021) - Bardi, Luca; Paolillo, Stefania; Bruzzese, Dario; Esposito, Cristina; Ambrosio, Antonio; Prastaro, Maria; Chirico, Alfonsina; Colella, Angela; Perrone-Filardi, Pasquale; Gargiulo, Paola
Abstract: Aims: Sodium–glucose co-transporter-2 inhibitors (SGLT2i) reduce cardiovascular (CV) events in diabetic patients, with a consistent effect on heart failure (HF) related outcomes. However, the effects on ischaemic CV events appear less certain, in particular in patients with history of HF. The aim of this meta-analysis is to investigate CV benefit of SGLT2i and to assess the effects in patients with and without established atherosclerotic cardiovascular disease (ASCVD), with and without HF, and with estimated glomerular filtration rate < or ≥ 60 mL/min. Methods: We searched PubMed, Embase, Cochrane, ISI Web of Science, SCOPUS, and clinicaltrial.gov databases. We performed a systematic review and meta-analysis of randomized, placebo-controlled, cardiovascular outcome trials (CVOT) of SGLT2i in diabetic patients, assessing the effects of SGLT2i on 3-point MACE [CV death, non-fatal myocardial infarction (MI), non-fatal stroke] and composite of HF hospitalization or CV death. Results: Of 205 articles, 7 CVOTs were included in the meta-analysis. Compared to placebo, SGLT2i significantly reduced by 10% the risk of 3-point MACE (HR 0.90; P  = 0.025) (Figure panel A) and the risk of CV death or HF hospitalization by 24% (HR 0.76; P  < 0.001) (Figure panel B). SGLT2i significantly reduced HF hospitalization by 30% (HR 0.70; P  < 0.001), with consistent effects in all subgroups analysed, CV death by 17% (HR 0.83; P  = 0.035) and all-cause mortality by 18% (HR 0.82; P  = 0.024). No significant effects were observed on MI and stroke. Conclusions: SGLT2i significantly reduce CV outcome in diabetic patients. SGLT2i remarkably and consistently reduce HF hospitalization, in patients with and without HF at baseline and independently on the presence of ASCVD.